PENINGKATAN KEMAMPUAN MENGANALISIS UNSUR INTRINSIK CERPEN MELALUI METODE DISKUSI JENIS BUZZ GROUP PADA SISWA KELAS VIII A SMP DWIJENDRA GIANYAR TAHUN PELAJARAN 2011/2012 - Sari, Ni Made Purnami; Suparsa, Ni Nyoman (Jurnal Santiaji Pendidikan (JSP), 2013)
This study is a classroom action research. It was conducted for the students at class VIII SMP DwijendraGianyar in the academic year 2011/2012. There were three cycles planned. There were 36 students. The object of the study was the improvement of ability in analyzing the intrinsic element of a short story through Buzz group discussion method. The results revealed that there was improvement in analyzing the intrinsic element of a short story after implementing Buzz group discussion method. It could be found from the mean score of the pretest was 4.2. It improved to 5.22 in the 1st cycle, then up to 6.22 in the 2nd cycle until achieving 7.38 in the 3rd cycle. It means that the standard-passing score (SKBM) that is 7.00 was achieved.